2019
DOI: 10.1128/jcm.00119-19
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Clinical Significance of Natural Variability in Hepatitis B Virus Reverse Transcriptase in Treatment-Naive Chinese Patients by Sanger Sequencing and Next-Generation Sequencing

Abstract: Mutations in hepatitis B virus (HBV) reverse transcriptase (RT) are associated with nucleos(t)ide analogue (NA) resistance during long-term antiviral treatment. However, the characterization of mutations in HBV RT in untreated patients has not yet been well illustrated. The objective of this study was to investigate the characterization and clinical significance of natural variability in HBV RT in treatment-naive patients. HBV RT sequences were analyzed in 427 patients by Sanger sequencing and in 66 patients b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 31 publications
1
11
1
Order By: Relevance
“…Through Sanger sequencing, our study assessed the influence on the types or frequency of mutations by HBV genotype, and discovered 14 genotype-dependent nucleotide polymorphic sites and 5 genotype-dependent AA polymorphic sites (Figure 1, Table S1, Table S2). In these findings, rt221, rt224, rt238 were identified to be genotype-dependent sites, as coincided with the reported literature [14,20]. rt222, rt223 were newly identified in Fujian, China and rarely reported in any other areas of China, strongly suggesting that geographical distribution of HBV genotypes would also be a contributing factor in HBV genome sequence discrepancies.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Through Sanger sequencing, our study assessed the influence on the types or frequency of mutations by HBV genotype, and discovered 14 genotype-dependent nucleotide polymorphic sites and 5 genotype-dependent AA polymorphic sites (Figure 1, Table S1, Table S2). In these findings, rt221, rt224, rt238 were identified to be genotype-dependent sites, as coincided with the reported literature [14,20]. rt222, rt223 were newly identified in Fujian, China and rarely reported in any other areas of China, strongly suggesting that geographical distribution of HBV genotypes would also be a contributing factor in HBV genome sequence discrepancies.…”
Section: Discussionsupporting
confidence: 88%
“…This discrepancy exists between studies correlated with the geographical or ethnic background of patients as well as viral genotype, implying a high genetic variability of HBV between various epidemic viral strains in different regions. Moreover, it was still noted that the direct-sequencing as population-based sequencing approach, might be restricted to detect major quasispecies more than 20% of the entire HBV populations, thus possibly leading to the undetection of the strains that were minor but functionally critical [19,20]. To confirm these minor strains, a high throughput sequencing detection may need to be performed.…”
Section: Discussionmentioning
confidence: 99%
“…Some of these positions had been reported previously, but others (rt82, rt214, and rt242) were not found in the corresponding genotype from previous studies. 5,15 The rt242 variant was only found in genotype B in a previous study 5 but was found only in genotype C in our study. Therefore, we speculated that different genotypes possessed different RT variants due to differences in evolutionary characteristics.…”
Section: Discussioncontrasting
confidence: 52%
“…Additionally, another study reported that AA polymorphic positions showed discrepancies in different areas in China. 15 These data indicated that the definition of genotype variants needs to take into account the reference sequences of different genotypes in different areas and the consensus sequence derived from local HBV isolates. Moreover, researchers have also suggested that some AA polymorphic positions could contribute to decreased viral replication and affect drug treatment outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation